2021
DOI: 10.3390/ijms222112090
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Pterygium and Pinguecula Reveals Evidence of Genomic Instability Associated with Chronic Inflammation

Abstract: Solar damage due to ultraviolet radiation (UVR) is implicated in the development of two proliferative lesions of the ocular surface: pterygium and pinguecula. Pterygium and pinguecula specimens were collected, along with adjacent healthy conjunctiva specimens. RNA was extracted and sequenced. Pairwise comparisons were made of differentially expressed genes (DEGs). Computational methods were used for analysis. Transcripts from 18,630 genes were identified. Comparison of two subgroups of pterygium specimens unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 114 publications
2
7
0
Order By: Relevance
“…In this study, we demonstrate the upregulation of TRPV3 expression in mouse model of skin injury induced by UVB radiation, further confirming a causative role of TRPV3 channel activation in UVB induced skin inflammation. A recent study of transcriptome analysis shows that TRPV3 gene upregulation is involved in proliferative lesions of ocular surface caused by ultraviolet radiation, 53 which is consistent with our findings in this study that TRPV3 upregulation is pathologically involved in the development of UV-induced skin inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we demonstrate the upregulation of TRPV3 expression in mouse model of skin injury induced by UVB radiation, further confirming a causative role of TRPV3 channel activation in UVB induced skin inflammation. A recent study of transcriptome analysis shows that TRPV3 gene upregulation is involved in proliferative lesions of ocular surface caused by ultraviolet radiation, 53 which is consistent with our findings in this study that TRPV3 upregulation is pathologically involved in the development of UV-induced skin inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…30 In addition, TRPV3 is highly upregulated in both pterygium and pinguecula induced by ultraviolet radiation, but not other TRP channels. 53 These observations further support the dominant role of Ca 2+ -permeable TRPV3 in UV-induced skin injury.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As photo-ageing is firmly associated with low-grade and long-lasting exposure, our studies privileged cultures at 5–8 passages (aged sister cells) [ 25 , 35 ]. Some studies reported the modulation of few pterygium-related genes in UV-exposed FBs, reinforcing the link between UV and initiation and/or progression of human pterygium and/or exacerbation of preexisting fibrosis [ 6 , 53 ]. In addition, ocular surface discomfort might also occur in the case of light (UV) reflected from snow, water, and sand [ 33 ].…”
Section: Discussionmentioning
confidence: 94%
“…The downregulation of some inflammatory and epigenetic factors by NGF might provide new opportunities for the development of targeted therapies. Herein, the interest was double, as most of the chronic exposures to solar UV rays are associated with exacerbation of existing ocular fibrosis (pterygium, pinguecula, squamous metaplasia, or carcinoma) or with some environment-associated dry eye forms [ 32 , 33 , 53 ]. NGF eye drop substitute might represent, in the near future, an alternative for protecting the ocular surface from UV lights [ 3 , 15 , 51 , 58 , 61 ].…”
Section: Discussionmentioning
confidence: 99%